Gestational Syphilis in Primary Care / Sífilis gestacional na Atenção Básica - Manoel Vitório Souza Santana; Priscila Nayara Gerônimo Barbosa; Jauan Fellipe Lima Santos (Diversitas Journal, 2019)
Gestational Syphilis is a Sexually Transmitted Infection transmitted by the bacterium Treponema pallidum that when untreated can result in early fetal death by vertical transmission; with SINAN registered 37,436 cases of syphilis present in gestation in 2017. Considering the nurse as an agent of prevention and health promotion, the objective of this study is to analyze the forms of prevention and treatment for syphilis in gestation applied by the nursing staff in a Basic Unit of Health in exploratory literary, answering the guiding question: "what nursing interventions contained in the literature about the prevention and treatment of gestational syphilis in primary care?". The method used was the bibliographic search in the databases LILACS, SCIELO and GOOGLE ACADEMICO, using the key words: gestational syphilis, nursing, prevention and treatment. The result of this study allowed to analyze 51 articles related to the theme, but excluding 31 articles that did not answer the guiding question; from the 20 articles, four responses were formulated for the writing of information: "screening and control of gestational syphilis; Health education; adherence to treatment of the couple; and prescription and drug administration. " The work concluded the relevant work of the nurse in the prevention of the disease, still in the gestation, and health promotion through the actions and interventions carried out in the Basic Health Unit.